Risk factors and spatial distribution of gastrointestinal parasites in backyard poultry production systems in central Chile - Cantin-Rosas, Bruno; Tomazic, Mariela Luján; Rodriguez, Anabel Elisa; Enciso, Nikita; Brante-Bernier, Juliette; Honores, Patricia; Godoy-Alfaro, Catalina; Abarca, Claudio; Alegría-Morán, Raúl; Ramírez-Toloza, Galia (MDPI, 2025)
Gastrointestinal parasites impact the health and productivity of domestic birds and may even be more common in production systems with lower biosafety conditions. In this context, backyard poultry production systems (BPPS), defined as small-scale family production systems, could be more affected. However, information about its epidemiology is limited in the Central Zone of Chile. This study aimed to determine the risk factors and spatial distribution of gastrointestinal parasites in BPPS in Central Chile. Thus, feces samples were collected from 51 backyards and analyzed using copro–parasitological techniques. In parallel, an epidemiological survey was conducted on the farmers, and the data were analyzed by multivariable logistic regression to identify risk factors. Spatial analysis was performed with the detected parasite species to determine high-risk clusters. Eimeria spp. was the most frequently detected parasite (72.5%), followed by Capillaria spp. (50.9%) and Ascaridia galli (49%). Regarding parasitic burden, nearly 90% of BPPS showed low parasitic burden for Eimeria spp. and helminths. In turn, the availability of potable drinking water (95% CI: 0.054–0.905; p = 0.036) and proper ventilation of the pens (95% CI: 0.003–0.429; p = 0.009) reduced the presence of parasites. Spatial high-risk clusters were detected for Eimeria spp. (RR = 2.60; p-value < 0.0001), A. galli (RR = 2.93; p-value = 0.021), and Trichostrongylus spp. (RR = 5.85; p-value = 0.050).